Process development for the laser powder bed fusion of WC‐Ni Cermets using sintered‐agglomerated powder. Issue 3 (11th January 2022) - Mendoza Jimenez, Edgar; Reeja‐Jayan, B.; Beuth, Jack
Abstract: Although ceramic particle‐metal matrix materials (i.e., cermets) can offer superior performance, manufacturing these materials via conventional means is difficult compared to the manufacturing of metal alloys. This study leverages the laser powder bed fusion (LPBF) process to additively manufacture dense tungsten carbide (WC)‐17 wt.% nickel (Ni) composite specimens using novel spherical, sintered‐agglomerated composite powder. A range of processing parameters yielding high‐density specimens was discovered using a sequential series of experiments comprised of single bead, multi‐layer, and cylindrical builds. Cylinders with a relative density >99% were fabricated and characterized in terms of microstructure, chemical composition, and hardness. Scanning electron microscopy images show favorable wetting between the Ni binder and carbide particles without any phase segregation and laser processing increased the average carbide particle size. Energy dispersive X‐ray and X‐ray diffraction analyses detected traces of secondary products after laser processing. For samples processed at high energy densities, complex carbides and carbon agglomerate phases were detected. The maximum hardness of 60.38 Rockwell C is achieved in the printed samples. The successful builds in this study open the way for LPBF of dense WC‐Ni parts with a large workable laser power‐laser velocity processing window.